Health‐related quality of life is unimpaired in children and adolescents with Marfan syndrome despite its distinctive phenotype. (12th January 2016) - Mueller, Goetz C.; Steiner, Kristoffer; Wild, Jeske M.; Stark, Veronika; Kozlik‐Feldmann, Rainer; Mir, Thomas S.
Abstract: Aim: Marfan syndrome (MFS) is a progressive, life‐threatening genetic disorder of the connective tissue, which causes impaired quality of life (QoL) in adults. This study investigated the quality of life in children and adolescents, taking into account their gender, age and how MFS affected their organs. Methods: This prospective nonrandomised single‐centre study included 46 patients with verified MFS with a mean age of 10.98 years (±3.72). QoL was measured using the self‐reported, multidimensional KINDL‐R questionnaire and compared with an age‐matched control group of 174 children and adolescents. Results: No significant overall reduction of QoL was found. Total QoL scores for patients diagnosed at four to seven years were the same as the control group (77.65 ± 9.37 versus 77.06 ± 11.72), but they were higher for patients aged eight to 16 years (75.15 ± 9.19 versus 70.46 ± 11.35, p = 0.025). No gender‐specific differences or impairments in QoL during adolescence were observed (p > 0.05). Analysis of the effect of organ manifestation on QoL showed better or equal QoL scores (p > 0.05), despite distinctive phenotypes such as ectopia lentis. Conclusion: QoL was fairly good in paediatric patients with MFS, and there was no impairment during adolescence. Despite the distinctive phenotype, quality of life was unimpaired in younger patients.